Endoscopic Total Thyroidectomy: Report of Two Cases - Aziz, M Mohibul; Khan, MA Wohab; Islam, Shamin (Journal of Bangladesh College of Physicians and Surgeons, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Two patients (one male and one female) recently under went total thyroidectomies using a standard laparoscope at the department of surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Three ports (one mid line and two laterals) were employed and a harmonic scalpel was used for the dissection. To the best of our knowledge, there was no report of endoscopic total thyroidectomy from Bangladesh. Both patients were fed on the first post operative day. They were discharged between the 3rd and 4th post operative days. There was no hypocalcaemia but one patient developed temporary unilateral vocal cord palsy. Endoscopic thyroidectomy appears to be a technically feasible patient friendly modality of treatment for the selected cases of thyroid swelling in an experienced hand with excellent out come. Key Words: Endoscopic; laparoscopic; thyroid surgery; total thyroidectomy. DOI: 10.3329/jbcps.v26i1.4233 J Bangladesh Coll Phys Surg 2008; 26: 46-49